Komparasi Pemikiran Aqidah Al-Asy’arī dan Ibnu Taimiyah Serta Revelansinya dengan Moderasi Beragama di Indonesia - Fiqi Restu Subekti (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study examines the core theological ideas of Abū al-Ḥasan al-Asy’arī and Ibn Taymiyyah, drawing from their respective seminal works, which serve as primary references in this research. The theological perspectives of Abū al-Ḥasan al-Asy’arī are derived from his book “al-Ibānah ‘an Uṣūl ad-Diyānah,’’ while Ibn Taymiyyah’s ideas are sourced from “al-‘Aqīdah al-Wāsiṭiyah.” This analysis aims to compare the key theological concepts of these two figures to identify their similarities and differences. Furthermore, the study will contextualize the thought processes of both figures within the framework of religious moderation in Indonesia. Employing a qualitative methodology, this research focuses on reviewing prior literature that has demonstrated high validity and credibility. The analysis reveals that Abū al-Ḥasan al-Asy’arī's paradigm is considerably more moderate compared to Ibn Taymiyyah's, which is categorized as extreme. In the context of religious moderation in Indonesia, it is found that the Nahdlatul Ulama group represents the ideas of Abū al-Ḥasan al-Asy’arī, while the Wahhabi group represents Ibn Taymiyyah's thought. Therefore, it is evident that the understanding and ideas of the Nahdlatul Ulama group are more relevant for implementation in Indonesia, as they are considered moderate and align with the concept of religious moderation.